Analysis of the Mineral Compositions of Lateritic Clay in Guangxi and their Influence - Er-jing Yang; Sha-sha Zeng; Hong-yan Mo; Cheng-lin Yang; Cheng Chen; Yan-fu Wang (Advances in Materials Science and Engineering)
In order to study the effect of mineral composition on the physical properties of lateritic clays, the mineral compositions of four kinds of lateritic clay from Guangxi province in China were quantitatively analyzed by means of DTA, XRD, SEM, XRF and total chemical element analysis. On this basis, the variation law of macroscopic physical properties of lateritic clay was analyzed from the perspective of mineralogy. The results show that kaolinite and goethite are the main minerals of lateritic clays from Guangxi in China. The mineral compositions of these four samples are quantitatively and accurately analyzed by Bogue’s method. According to the study on mineral compositions of soil samples, the physical properties of lateritic clay are related to its clay minerals and cemented substances. The liquid limit (LL) or plastic limit (PL) increases with the increase of the ability and content of clay minerals to adsorb water. The lateritic clay is dominated by kaolinite minerals with low adsorption capacity, so the observed boundary water content (LL and PL) of high value of lateritic clays can be explained by the contribution of “inert water” in soil pores. The iron-bonded cement minerals (the form of existence is goethite) in lateritic clay have great influence on the liquid and plastic limits, which decrease linearly with the increase of goethite, whereas the goethite has relatively smaller effect on shrinkage characteristics. It is believed that the shrinkage characteristics of lateritic clay may also be affected by other factors.